The Role of Second Language Reading Proficiency in Moderating Second Language Word Recognition - Xiaomeng Li; Tianxu Chen (Education Sciences, 2024)
Drawing upon the division of labor between orthographic and phonological information, this study investigated whether and how L2 reading proficiency moderates learners’ reliance on phonological and orthographic information in retrieving word meanings. A total of 136 Chinese collegiate students who learned English as a foreign language (EFL) completed English reading proficiency tests and were divided into higher and lower reading proficiency groups using an extreme-group approach. Behavioral tasks were used to measure the participants’ sensitivity to and processing skills of orthographic and phonological information. The analysis showed that the reliance on phonological and orthographic information differed significantly across L2 reading proficiency groups: The higher reading proficiency group was sensitive to both phonological and orthographic information within words, while the lower reading proficiency group was only sensitive to orthographic information; only orthographic processing skills significantly contributed to the word meaning retrieval of individuals in the higher reading proficiency group, while phonological processing skills were the only predictor for the lower reading proficiency group. These results suggest that the use of phonological and orthographic information vary as a function of L2 learners’ English reading proficiency. Implications regarding the changing patterns of L1 influences and the language-universal and language-specific aspects of word recognition were discussed.